Successful Grafting in a Patient With Recalcitrant Pemphigus: A Case Report. Issue 2 (1st May 2014) - Stiefel, Daniel B.; Saavedra, Arturo; Elliott, Jennifer A.; Reich, Peter
Abstract : Introduction: This article reports the successful management of a gingival graft in a patient with both oral manifestations of chronic systemic disease and oral sequelae of chemotherapy. In addition to proper clinical technique, a case such as this requires clear communication among health care providers and a sustained program of symptom‐specific oral hygiene. Case Presentation: A patient with pemphigus vulgaris (PV) who was in remission after 7 years of treatment presented with a periodontal abscess. Concerned that a fatal infection could originate from the tooth in this immunocompromised patient, the treating physician referred the patient to a periodontist for a gingival graft. Throughout, candid communication among periodontist, physician, and patient produced improvements in an already deliberate approach to oral hygiene. In the presence of persistent chronic disease and associated oral inflammation, a patient‐specific oral‐hygiene regimen including non‐traditional methods can contribute to a successful outcome. Conclusions: This successful procedure demonstrates that a history of PV is not a contraindication to periodontal surgery, such as grafting, as long as prophylactic immunosuppression, assiduous oral hygiene, and close clinical follow‐up are performed. A gingival graft is a viable procedure in patients with PV and can be another tool in the toolkit of treatments for mucocutaneous disorders.